PENGARUH KUALITAS PEMBELAJARAN DAN INTENSITAS MEMBACA TERHADAP HASIL BELAJAR MATA PELAJARAN AL-QUR’AN HADITS SISWA MI KECAMATAN DONOROJO KABUPATEN JEPARA - Djaring Subondo; Barowi Barowi; Moh Nasuka; Munasir Munasir (Intelegensia : Jurnal Pendidikan Islam, 2020)
AbstractThis research is aimed to find out how big the influence of learning quality toward Qur’an Hadits learning output, to find out how big the influence of reading intensity toward Qur’an Hadits learning output, and to find out how big the influence of learning quality and reading intensity toward Qur’an Hadits learning output of MI students in Donorojo Sub-district Jepara Regency. This research is quantitative research with the kind of field research. Data obtained by interview, documentation, and questionnaire. Data analyzed by using quantitative analysis. The obtained data then analyzed using three analysis techniques, which are preliminary analysis, hypothesis analysis, and advanced analysis. Based on the result of research, it is known that: 1) Learning quality affects the Qur’an Hadits learning output. Shown by the correlation coefficient of 0.57 while the simultaneous contribution is 0.325 and the remaining 0.675 is determined by other variables. (2) Reading intensity affects the learning outcomes of the Al-Qur'an Hadith. Shown by the correlation coefficient is 0.582 while the contribution simultaneously is 0.339 and the remaining 0.661 is determined by other variables. (3) Learning quality and reading intensity affect the learning outcomes of the Qur'an. The correlation coefficient is shown to be 0.662 while the simultaneous contribution is 0.438 or the remaining 0.562 is determined by other variables.Keywords: Reading Intensity; Learning Quality; Learning Outcomes